Efficacy of a telehealth cognitive behavioral therapy for improving sleep and nightmares in children aged 6–17 - Cromer, Lisa DeMarni; Bell, Sarah Beth; Prince, Lauren E.; Hollman, Nicholas; El Sabbagh, Elissar; Buck, Tara R. (Frontiers in Sleep, 2024)
Introduction: This study examined the efficacy of a five-module cognitive behavioral therapy for improving sleep and nightmares in children (CBT-NC).Materials and Methods: Forty-six youth aged 6 -17 years with sleep problems and at least weekly chronic and distressing nightmares were randomized to treatment (n = 23) or waitlist (n = 23) using a block four randomized design. Sixty-five percent of participants (n = 30) were White, 4% (n=2) were Black/African American, 2% (n = 1) were Asian American, 13% (n = 6) were Native American or Pacific Islander, and 15% (n = 7) were multi-racial. Fifty percent of participants (n = 23) were cisgender girls, 35% were cisgender boys (n = 16), 7% were transgender boys (n = 3), and 9% were gender nonbinary (n = 4). Baseline nightmare persistence ranged from 6 months to 13.5 years. Treatment adapted exposure, relaxation, and rescription therapy for trauma-related nightmares in adults and added elements of cognitive behavioral therapy for insomnia in children. Psychoeducation included topics of sleep and nightmares, relaxation, anxiety management, and sleep hygiene; youth were guided through nightmare exposure and rescription.Results: There was a statistically significant improvement in number of nights with awakening (Cohen's d = 1.08.99), number of weekly nightmares (Cohen's d = .820) and nightmare distress (Cohen's d = 1.05.96) for treatment compared to waitlist. Parent-reported youth sleep improved for the entire group from pre-treatment to post-treatment (p <= 0.0013) but did not reach statistical significance for between subject analyses of treatment group compared to waitlist (p = 0.05). Between subject analyses saw improvement for the treatment group compared to waitlist on internalizing and externalizing problems and suicidal thoughts and behaviors.Discussion: This study supports the efficacy of CBT-NC for improving sleep maintenance, nightmare frequency and distress, and other mental health difficulties in youth. Preliminary evidence of possibly improving suicidal thinking and behavior is also presented.